A journey into the world of small RNAs in the arbuscular mycorrhizal symbiosis - Ledford, William Conrad; Silvestri, Alessandro; Fiorilli, Valentina; Roth, Ronelle; Rubio‐Somoza, Ignacio; Lanfranco, Luisa (The New phytologist, 2024)
Summary Arbuscular mycorrhizal (AM) symbiosis is a mutualistic interaction between fungi and most land plants that is underpinned by a bidirectional exchange of nutrients. AM development is a tightly regulated process that encompasses molecular communication for reciprocal recognition, fungal accommodation in root tissues and activation of symbiotic function. As such, a complex network of transcriptional regulation and molecular signaling underlies the cellular and metabolic reprogramming of host cells upon AM fungal colonization. In addition to transcription factors, small RNAs (sRNAs) are emerging as important regulators embedded in the gene network that orchestrates AM development. In addition to controlling cell‐autonomous processes, plant sRNAs also function as mobile signals capable of moving to different organs and even to different plants or organisms that interact with plants. AM fungi also produce sRNAs; however, their function in the AM symbiosis remains largely unknown. Here, we discuss the contribution of host sRNAs in the development of AM symbiosis by considering their role in the transcriptional reprogramming of AM fungal colonized cells. We also describe the characteristics of AM fungal‐derived sRNAs and emerging evidence for the bidirectional transfer of functional sRNAs between the two partners to mutually modulate gene expression and control the symbiosis.